Insertion of Retrotransposons at Chromosome Ends: Adaptive Response to Chromosome Maintenance - Servant, Geraldine; Deininger, Prescott L. (Frontiers in Genetics, 2016)
The telomerase complex is a specialized reverse transcriptase that inserts tandem DNA arrays at the linear chromosome ends and contributes to the protection of the genetic information in eukaryotic genomes. Telomerases are phylogenetically related to retrotransposons, encoding also the reverse transcriptase activity required for the amplification of their sequences throughout the genome. Intriguingly the telomerase gene is lost from the drosophila genome and tandem retrotransposons replace telomeric sequences at the chromosome extremities. This observation suggests the versatility of reverse transcriptase activity in counteracting the chromosome shortening associated with genome replication and that retrotransposons can provide this activity in case of a dysfunctional telomerase. In this review paper, we describe the major classes of retroelements present in eukaryotic genomes in order to point out the differences and similarities with the telomerase complex. In a second part, we discuss the insertion of retroelements at the ends of chromosomes as an adaptive response for dysfunctional telomeres.